Terra-i Ethiopia - Mulatu, Kalkidan Ayele; Ayehu, Getachew Tesfaye; Paz Garcia, Paula Andrea; Perez Escobar, Jorge Andres; Tello Dagua, Jhon Jairo; Kassa, Habtemariam (2024)
Terra-i Ethiopia, is a tool customized to detect forest change and loss vegetation in near-real-time for providing early warning on forest losses in Ethiopia.